Processing and nutritional chemical and technological evaluation of precoced product based pota (Dosidicus gigas) - Hernandez F, Eloisa M. (2018)
The squid (Dosidicus gigas) is a cephalopod mollusk, a source of high quality proteins that is currently underexploited. The objective was to develop the methodology for the elaboration of a pre-cooked pota product, to evaluate the digestibility of the proteins and the shelf life of the product. Methodology: In a descriptive and experimental design, the nutritional technological study was carried out. Two samples of squid each consisting of 5 kg of the mantle, acquired at the Callao Fishing Terminal, were processed and analyzed independently. The process flow included: disinfection, cutting, washing, stabilization, cutting into strips, cooking by immersion in vegetable oil, packaging and storage. The physical and chemical analysis, using AOAC techniques; minerals using GBC Avanta atomic absorption spectrophotometer with graphite furnace. The digestibility by enzymatic method. The sensory analysis, by descriptive method. The microbiological analysis, according to national and international criteria. The most relevant results (%) in the fresh sample and in the pre-cooked product were: water, 80,2g and 42,9g; 16g and 43,0g proteins; protein digestibility, 87 and 89% respectively. Lead and cadmium not detectable. According to taste and smell attributes, between 51 and 76% of the evaluation panel categorized the precooked product as “pleasant”. The useful life was 30 days. The microbiological analysis: Aerobic mesophiles; 2 x 10 cfu / g; E. coli absent; Staphylococcus aureus, absent; Salmonella sp in 25 g., Absent. The characteristics of the pre-cooked pota-based product show the nutritional potential of the squid for conserving the quality of the proteins and to be acceptable and innocuous.